Time Perception and Emotion: The Effect of Task Difficulty - Kaur, Ameek (My University, 2023)
Time perception refers to an individual's subjective experience of the passage of time. It is measured by their own perception of the duration of an event. While physical time is relatively objective, psychological time is subjective. Task difficulty refers to a person's subjective judgment of the complexity of a task, while task complexity represents the cognitive demands of a task. Although the influence of stimulus properties (such as emotion, color, sound, magnitude, and so on) on temporal perception has been extensively studied, it remains unclear whether task-related properties can modulate temporal processing. In other words, how does the inherent task demand (in this case, discrimination) affect the subjective experience of time? Whether the subjective judgment of time is affected by the task demand or by the stimulus properties such as emotion. Therefore, the present study examines the influence of emotion on temporal perception across different task conditions (easy discrimination vs difficult discrimination). The hypothesis states that if stimulus properties always affect temporal perception, we would not observe a differential effect of emotion on different task conditions (easy discrimination vs difficult discrimination). The results suggest that in the easy temporal task, emotion does not modulate our temporal judgment. However, when the temporal task condition is difficult, stimulus affectivity becomes apparent, leading to an overestimation of time for angry stimuli than that of neutral stimuli. Thus, we can conclude that it is the temporal task condition (easy or difficult) that primarily controls our temporal perception in this experiment. The attentional gate model is discussed as a theoretical framework to explain these findings and provide a conceptual understanding of the relationship between task conditions, emotion, and temporal perception.
Keywords: Time Perception; Emotion; Task conditions